1992
DOI: 10.1111/j.1365-2672.1992.tb04972.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantitative analysis of degradation products of chlorhexidine with chlorhexidine‐resistant bacteria with three‐dimensional high performance liquid chromatography

Abstract: The products of the degradation of chlorhexidine by two chlorhexidine‐resistant strains of Achromobacter xylosoxidans, isolated from an ultrasonic hand washer, were identified by three‐dimensional HPLC. In the degradation process a pathway forming p‐chlorophenol, probably through p‐chloroaniline, was also observed, as was a pathway forming phenol and pyrogallol. The quantitative measurement of these products at their maximum absorption spectra by two‐dimensional HPLC suggested the presence of chlorhexidine‐deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…The nature and composition of these layers depend on the organism type and may act as a permeability barrier, in which there may be a reduced uptake (422,428). Alternatively but less commonly, constitutively synthesized enzymes may bring about degradation of a compound (43,214,358). Intrinsic (innate) resistance is thus a natural, chromosomally controlled property of a bacterial cell that enables it to circumvent the action of an antiseptic or disinfectant.…”
Section: Intrinsic Bacterial Resistance Mechanismsmentioning
confidence: 99%
“…The nature and composition of these layers depend on the organism type and may act as a permeability barrier, in which there may be a reduced uptake (422,428). Alternatively but less commonly, constitutively synthesized enzymes may bring about degradation of a compound (43,214,358). Intrinsic (innate) resistance is thus a natural, chromosomally controlled property of a bacterial cell that enables it to circumvent the action of an antiseptic or disinfectant.…”
Section: Intrinsic Bacterial Resistance Mechanismsmentioning
confidence: 99%
“…Impermeability of the outer membrane to chlorhexidine has been implicated in Pseudomonas, Proteus, and Providencia (12,18 (12,18). A chlorhexidine-degrading enzyme has been discovered in Achromobacter xylosoxidans (14). We demonstrated that transformation of cepA-containing phagemid into XLOLR resulted in significant elevation of chlorhexidine MICs.…”
mentioning
confidence: 85%
“…and Providencia stuartii (Russell & Russell 1995;Russell & Chopra 1996;Russell et al 1997;McDonnell & Russell 1999;Stickler & King 1999). It has also been proposed that chlorhexidine-resistant bacteria can degrade the bisbiguanide (Ogase et al 1992). Physiological (phenotypic) adaptation can modulate the intrinsic insusceptibility of cells to biocides, e.g.…”
Section: Mechanisms Of Bacterial Resistance To Biocidesmentioning
confidence: 99%